Adaptive control of robotic arm carrying uncertain time-varying payload based on function approximation technique - Zainul Azlan, Norsinnira; Sayed Jaafar, Syarifah Nurul Syuhada (Springer Verlag, 2014)
This paper presents a new adaptive controller based on the Function Approximation Technique (FAT) for a 2 degree of freedom (DOF) robot arm carrying uncertain time-varying payload. The mathematical model of the arm is expressed as the summation of the known and the uncertain terms in deriving the proposed control law. The time-varying uncertainty is expressed using an FAT expression, which avoids the need of linear parameterization of the mathematical model of the robotic arm. The expression also allows the update law to be easily derived by an appropriate choice of Lyapunov-like function. The stability proof of the controller is described in detail and computer simulation results are presented to demonstrate the effectiveness of the proposed technique.